A multimethod approach to the study of Classic Maya houselots and land tenure: Preliminary results from the Three Rivers Region, Belize. (August 2021) - Kwoka, Joshua J.; Guderjan, Thomas H.; Eshleman, Sara; Ruhl, Thomas; Telepak, Justin; Beach, Timothy; Luzzadder-Beach, Sheryl; McClatchey, Will; Bascopé, Grace
Highlights: Study combines excavations with lidar and qualitative soil phosphorus surveys. Linear stone features appear to demarcate ancient Maya houselots. Mean interior area of proposed houselots is large in comparison to other regions. Dense settlement and larger houselots may signal decreased use of outfields. Data may indicate the existence of private land tenure during the Late Classic period. Abstract: Results of a recent lidar survey of northwestern Belize revealed a heavily modified anthropogenic landscape populated by dense ancient Maya settlement. Most surprising was the detection of an extensive network of landesque capital in form of linear stone features, with 87.8 linear km identified to date. While likely multifunctional, many of these features appear to delineate residential space and are similar in appearance to contemporary Maya houselots. This paper presents the results of a pilot project designed to collect preliminary data on houselots utilizing multiple research methods. Despite differences in land use and vegetation among the study loci, ground truthing results suggest the lidar data are high fidelity. Excavations produced mixed results, with architectural excavations providing the broadest array of data, including evidence that two of the houselots were occupied during the Late Classic (AD 600 – 850) period. Qualitative soil tests for available phosphorus detected elevated levels in areas that are consistent with middens and kitchen gardens. In addition, microtopographic anomalies were identified that may have represented an important household resource. A synthesis of the available data results in a view of large houselots with broad agricultural resource bases. Finally, settlement density and the ubiquity of demarcated houselots may signal the existence of a restricted-use land tenure system.